2016
DOI: 10.1002/stem.2498
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: The Use of Adipose-Derived Stromal Vascular Fraction Cells and Platelet Rich Plasma in Regenerative Plastic Surgery

Abstract: Tissue engineering has emerged at the intersection of numerous disciplines to meet a global clinical need for technologies to promote the regeneration of tissues. Recently, many authors have focused their attention on mesenchymal stem/stromal cells (MSCs) for their capacity to differentiate into many cell lineages. The most widely studied cell types are bone marrow mesenchymal stem cells and adipose‐derived stem cells (ASCs), which display similar results. Biomaterials, cells, and growth factors are needed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
111
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(113 citation statements)
references
References 170 publications
(224 reference statements)
0
111
0
2
Order By: Relevance
“…Also, it has been reported that impaired angiogenesis is the cause of refractory wounds [36]. Studies have suggested that MSC-based therapies with platelet-rich plasma are able to promote wound healing by enhanced angiogenesis [37,38]. Furthermore, the clinical studies reported by Cervelli et al (2010) and Nicoli et al (2013) have demonstrated that the use of a three-dimensional matrix of hyaluronic acid with platelet-rich plasma can enhance tissue proliferation and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been reported that impaired angiogenesis is the cause of refractory wounds [36]. Studies have suggested that MSC-based therapies with platelet-rich plasma are able to promote wound healing by enhanced angiogenesis [37,38]. Furthermore, the clinical studies reported by Cervelli et al (2010) and Nicoli et al (2013) have demonstrated that the use of a three-dimensional matrix of hyaluronic acid with platelet-rich plasma can enhance tissue proliferation and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro differentiation to chondroblasts, adipocytes and osteoblasts is the third hallmark of MSCs/ADSCs , which was addressed in a further step.…”
Section: Discussionmentioning
confidence: 99%
“…The term ADSC describes a population of multipotent cells derived from adipose tissue with characteristics of mesenchymal stem/stromal cells (MSCs) . MSCs have to meet three criteria, as defined by the Mesenchymal and Tissue Stem Cell Committee of the International Society for Cellular Therapy (ISCT) : they have to (i) be plastic adherent, (ii) express a panel of defined cell surface markers, (iii) differentiate to osteoblasts, adipocytes and chondroblasts in vitro .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ADSCs secrete a wide range of growth factors that can stimulate tissue regeneration. Therefore, the clinical use of ASCs is feasible [51]. …”
Section: Discussionmentioning
confidence: 99%